SOSIALISASI KEBIJAKAN DAN PROGRAM KEMENTERIAN KELAUTAN DAN PERIKANAN PADA PENGUNJUNG KOTA TUA JAKARTA BARAT - Riswandi Riswandi; Sofia Aunul; Rahmadya Putra Nugraha (Universitas Mercu Buana, 2018)
Since appointed and inaugurated by President Jokowi as the Minister of Marine Affairs and Fisheries (KKP) of the Republic of Indonesia, Susi Pudjiastuti affirmed that the policy of the Ministry of Marine Affairs and Fisheries has been in accordance with the vision and mission of the government led by President Jokowi who prioritizes the sea. According to Susi, the CTF policy that focuses on overcoming the crime of fish theft is the right step to realize the sea as the future. The Indonesian people, on the one hand, put great hopes on the figure of Susi Pudjiastuti in making corrections to the marine problem of Indonesia, because he is considered to have the courage and competence as a minister of marine and fisheries. In fact, not only in this country the minister gets support, even at the global level he gets a lot of sympathy and support. However, on the other hand, some parties have not understood the policies and programs that have been and are being implemented by the CTF under Susi Pudjiastuti, even many who judge the policy measures issued Susi Pudjiastuti this controversial and dilemmatic. Susi policy was apparently received a negative response from the fishermen. A number of fishermen's representatives rallied in front of the Merdeka Palace and were received by Chief of Staff of PresidentTeten Masduki on July 11, 2017. Through the banners and speeches the protesters requested that President Jokowi cancel the policy of Minister KKP Susi Pudjiastuti about the ban cantrang as fishing gear fish. Kota Tua is one of the tourist attractions which is a Jakarta landmark that stores various relics of the past problems of high value. Not only domestic tourists, but foreign tourists also like to set foot in the Old Town tourist attractions. Based on the aforementioned thinking, Broadcasting Study Area of FIKOM UMB sees prelu implemented Activitiesof Service in the form of Training with Effective Communication theme as School Learning Method with target audience of teachers in West Jakarta and Tangerang area. The results of the devotional activity through the distribution of questionnaires to the visitors of Kota Tua indicate that the public know and understand the policies and programs of the Ministry and Maritime Minister Susi Pudjiastuti, and they also support the policies and programs implemented by the ministry, especially the sinking program of foreign ships thieves fish.